2012
DOI: 10.2151/jmsj.2012-516
|View full text |Cite
|
Sign up to set email alerts
|

Microphysical Properties of Maritime Squall Line Observed on June 2, 2008 in Taiwan

Abstract: The physical characteristics of rain are reflected by the shape of the raindrop size distribution (RDSD). Specifically, the RDSD is the result of different precipitation formation processes. We measured the RDSD at the surface in heavy rainfall during SoWMEX/TiMREX (2008) in Taiwan. The heavy rainfall was characterized by a squall line accompanied by trailing stratiform precipitation, and it was partitioned into three regions based on radar reflectivity patterns: convective line, stratiform, and reflectivity t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 41 publications
0
33
0
Order By: Relevance
“…As the squall line passes the PARSIVEL, the convective region of the squall line is subdivided into three segments: LE, CC, and TE, as illustrated in Figure using the criteria in Jung et al . []. For LE, the concentration of raindrops is the lowest among the three segments with the maximum drop diameter ( D max ) ~4 mm (Figure a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As the squall line passes the PARSIVEL, the convective region of the squall line is subdivided into three segments: LE, CC, and TE, as illustrated in Figure using the criteria in Jung et al . []. For LE, the concentration of raindrops is the lowest among the three segments with the maximum drop diameter ( D max ) ~4 mm (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…Disdrometers and polarimetric radars have been extensively used to derive DSDs and other microphysical properties, including mass‐weighted diameter ( D m ), logarithmic normalized intercept (log 10 N w ), and liquid water content (LWC), respectively [ Bringi et al ., ; Rosenfeld and Ulbrich , ]. The DSD characteristics of squall lines have been studied in many field campaigns throughout the world, such as the South China Sea Monsoon Experiment (SCSMEX) in Asia [ Wang and Carey , ], the African Monsoon Multidisciplinary Analysis (AMMA) in Mexico [ Evaristo et al ., ], the Midlatitude Continental Convective Clouds Experiment (MC3E) in the United States [ Wang et al ., ], and the Southwest Monsoon Experiment/Terrain‐influenced Monsoon Rainfall Experiment (SoWMEX/TiMREX) in Taiwan [ Jung et al ., ]. Early studies used ground‐based disdrometers to derive DSDs within passing squall lines and revealed DSDs in three regions, convection, transition, and stratiform [e.g., Uijlenhoet et al ., ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is due to the reduction in the riming of cloud water by graupel compared to the accretion of cloud water by rain. The large IWC in the downdraught regions of the warmer temperature regime is where graupel is expected, which is often located behind and below the convective updraughts (Barnes and Houze, 2014), where the suggestion is that these larger particles help to generate downdraughts through mass loading (Franklin et al, 2005;Jung et al, 2012). This argument is supported by analysis of the downdraught IWC that shows that the majority of the ice in the downdraughts is graupel.…”
Section: Phase Composition and Comparison With In Situ Observationsmentioning
confidence: 91%
“…In all rain rate classes, Palau rainfall has higher values of N w , μ, and Λ and Taiwan rainfall has higher D m values. Similar type of results were reported by Jung et al (2012) for a squall line in south Taiwan. They found higher (lower) values of D m (N w , μ, and Λ) in convective region of the Taiwan squall line than tropical oceanic storms.…”
Section: 1002/2017jd026816mentioning
confidence: 99%